Gα/GSA-1 works upstream of PKA/KIN-1 to regulate calcium signaling and contractility in the Caenorhabditis elegans spermatheca - Castaneda, Perla G. (PLoS Genet, 2020)
Correct regulation of cell contractility is critical for the function of many biological systems. The reproductive system of the hermaphroditic nematode C. elegans contains a contractile tube of myoepithelial cells known as the spermatheca, which stores sperm and is the site of oocyte fertilization. Regulated contraction of the spermatheca pushes the embryo into the uterus. Cell contractility in the spermatheca is dependent on actin and myosin and is regulated, in part, by Ca(2+) signaling through the phospholipase PLC-1, which mediates Ca(2+) release from the endoplasmic reticulum. Here, we describe a novel role for GSA-1/Gα(s,) and protein kinase A, composed of the catalytic subunit KIN-1/PKA-C and the regulatory subunit KIN-2/PKA-R, in the regulation of Ca(2+) release and contractility in the C. elegans spermatheca. Without GSA-1/Gα(s) or KIN-1/PKA-C, Ca(2+) is not released, and oocytes become trapped in the spermatheca. Conversely, when PKA is activated through either a gain of function allele in GSA-1 (GSA-1(GF)) or by depletion of KIN-2/PKA-R, the transit times and total numbers, although not frequencies, of Ca(2+) pulses are increased, and Ca(2+) propagates across the spermatheca even in the absence of oocyte entry. In the spermathecal-uterine valve, loss of GSA-1/Gα(s) or KIN-1/PKA-C results in sustained, high levels of Ca(2+) and a loss of coordination between the spermathecal bag and sp-ut valve. Additionally, we show that depleting phosphodiesterase PDE-6 levels alters contractility and Ca(2+) dynamics in the spermatheca, and that the GPB-1 and GPB-2 G(β) subunits play a central role in regulating spermathecal contractility and Ca(2+) signaling. This work identifies a signaling network in which Ca(2+) and cAMP pathways work together to coordinate spermathecal contractions for successful ovulations.